(untitled) - Griffin, Laura; 1973- (Thorndike, Maine, 2021)
"When a woman is found brutally murdered on Austins lakeside hike-and-bike trail, investigative reporter Bailey Rhoads turns up on the scene demanding access and answers. She tries to pry information out of the lead detective, Jacob Merritt. But this case is unlike any hes ever seen, and nothing adds up. With the pressure building, Jacob knows the last thing he needs is a romantic entanglement, but he cant convince himself to stay away from Bailey. Bailey has a hunch that the victim wasnt who she claimed to be and believes this mugging-turned-murder could have been a targeted hit. When she digs deeper, the trail leads her to a high-tech fortress on the outskirts of Austin, where researchers are pushing the boundaries of a cutting-edge technology that could be deadly in the wrong hands. As a ruthless hit mans mission becomes clear, Bailey and Jacob join together in a desperate search to locate the next target before the clock ticks down in this lethal game of hide-and-seek"--
Keywords: Fiction; Murder; Investigation; Police; Fiction; Reporters and reporting; Fiction; Austin (Tex.); Fiction; Detective and mystery fiction; Thrillers (Fiction); Romance fiction; Romantic suspense fiction; Romance fiction; Fiction; Detective and mystery fiction; Thrillers (Fiction)